Advancements in the use of Auger electrons in science and medicine during the period 2015–2019. (2nd January 2023) - Howell, Roger W.
Abstract: Auger electrons can be highly radiotoxic when they are used to irradiate specific molecular sites. This has spurred basic science investigations of their radiobiological effects and clinical investigations of their potential for therapy. Focused symposia on the biophysical aspects of Auger processes have been held quadrennially. This 9th International Symposium on Physical, Molecular, Cellular, and Medical Aspects of Auger Processes at Oxford University brought together scientists from many different fields to review past findings, discuss the latest studies, and plot the future work to be done. This review article examines the research in this field that was published during the years 2015–2019 which corresponds to the period since the last meeting in Japan. In addition, this article points to future work yet to be done. There have been a plethora of advancements in our understanding of Auger processes. These advancements range from basic atomic and molecular physics to new ways to implement Auger electron emitters in radiopharmaceutical therapy. The highly localized doses of radiation that are deposited within a 10 nm of the decay site make them precision tools for discovery across the physical, chemical, biological, and medical sciences.